1991
DOI: 10.1007/bf01665309
|View full text |Cite
|
Sign up to set email alerts
|

Subtotal parathyroidectomy versus total parathyroidectomy and autotransplantation in secondary hyperparathyroidism: A randomized trial

Abstract: In a randomized study subtotal parathyroidectomy (sPTX) was compared with total parathyroidectomy and autotransplantation of fresh tissue (PTX + AT) in 40 patients with severe secondary hyperparathyroidism (HPT). After surgery both groups were followed at 19 +/- 6 months (PTX + AT) and 19 +/- 7 months (sPTX) and at 43 +/- 9 months (PTX + AT) and 40 +/- 7 months (sPTX). There were 17 patients alive in each group at the time of the second follow-up. After sPTX, 2 patients required re-operation because of recurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
157
1
22

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(188 citation statements)
references
References 23 publications
5
157
1
22
Order By: Relevance
“…As glândulas paratireóides quando removidas no curso da cirurgia da tireóide, possuem uma alternativa adequada para o implante autólogo 1 .…”
Section: Discussionunclassified
“…As glândulas paratireóides quando removidas no curso da cirurgia da tireóide, possuem uma alternativa adequada para o implante autólogo 1 .…”
Section: Discussionunclassified
“…Another advantage is that the site of recurrence can be assessed by a Casanova autograftectomy test [37] or its simplified modification [38]. The only prospective randomized trial comparing the outcome of 40 patients with either subtotal PTX or TPTX+AT showed significantly decreased rates of recurrence, significantly more often normalization of serum calcium and alkaline phosphatase as well as significant improvement of clinical signs like pruritus and muscle weakness after TPTX+AT compared to subtotal PTX [39] (EL IB). However, this RCT was underpowered to lead to standardization of this operative approach.…”
Section: Surgical Concepts In Renal Hyperparathyroidismmentioning
confidence: 99%
“…The most common surgical procedures used currently to treat renal hyperparathyroidism are subtotal parathyroidectomy and total parathyroidectomy with intramuscular implantation of parathyroid tissue [15]. A small amount of abnormal parathyroid tissue is left in the patient with both techniques.…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective, randomized, clinical trial, Rothmund et al [15] compared 20 cases of subtotal parathyroidectomy with 20 cases of total parathyroidectomy and intra-muscular autotransplantation followed up for a mean duration of more than 40 months. Hypercalcemia was less frequent and no patient underwent another operation after the latter procedure [16,17].…”
Section: Discussionmentioning
confidence: 99%